2011
DOI: 10.1051/0004-6361/201015273
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian timing analysis of giant flare of SGR  180620 by RXTE PCA

Abstract: Aims. By detecting high-frequency quasi-periodic oscillations (QPOs) and estimating their frequencies during the decaying tail of giant flares from soft gamma-ray repeaters (SGRs) useful constraints for the equation of state (EoS) of superdense matter may be obtained via comparison with theoretical predictions of eigenfrequencies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 31 publications
(54 reference statements)
4
31
0
Order By: Relevance
“…As first pointed out by Sotani et al (2008a), the interpretation of the frequencies 30, 92 and 150 Hz in SGR 180620 in terms of the , and QPOs is very tempting. Here we note that the 18 Hz oscillation may be interpreted as the first edge QPO , which for model APR+DH has a frequency of about Hz (this could also correspond to the frequency at 16.9 Hz found by Hambaryan et al 2011). Similarly, the 36.4 Hz oscillation could be interpreted as the QPO.…”
Section: Summary and Discussionsupporting
confidence: 69%
“…As first pointed out by Sotani et al (2008a), the interpretation of the frequencies 30, 92 and 150 Hz in SGR 180620 in terms of the , and QPOs is very tempting. Here we note that the 18 Hz oscillation may be interpreted as the first edge QPO , which for model APR+DH has a frequency of about Hz (this could also correspond to the frequency at 16.9 Hz found by Hambaryan et al 2011). Similarly, the 36.4 Hz oscillation could be interpreted as the QPO.…”
Section: Summary and Discussionsupporting
confidence: 69%
“…Three such giant bursts have been detected so far. In their afterglow, in addition to the modulation associated with the magnetar's rotation, several quasiperiodic oscillations (QPOs) in the frequency range from 18-1800 Hz were observed [8][9][10][11][12]. These oscillations have been interpreted as torsional shear modes of the crust [13].…”
Section: Frequencies Of the Fundamental Crustal Shear Modementioning
confidence: 99%
“…In this paper, I focus on shear properties of the neutron-star crusts: The shear modulus µ, shear velocities v S , and the frequency spectrum of crustal shear modes. Crustal shear modes are of particular interest for the description of quasiperiodic oscillations (QPOs) in the afterglow of giant γ-ray bursts in magnetars [8][9][10][11][12]. The shear modulus describes how the neutron-star crust elastically deforms under shear stress, i.e., it describes the stiffness of the crust lattice under shear deformations.…”
Section: Introductionmentioning
confidence: 99%
“…Fourier amplitude at one point inside the crust r = 9.4 km and θ = 0.6. The dashed red lines indicate the frequencies of the observed QPOs during the giant flare of SGR 1806-20, the blue lines show additional frequencies found byHambaryan et al (2011), and the green line shows the frequency found in normal bursts byHuppenkothen et al (2014c). Plus (minus) signs indicate oscillations that are symmetric (antisymmetric) in Bϕ w.r.t.…”
mentioning
confidence: 99%